2021
DOI: 10.1016/j.drugalcdep.2021.108986
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a therapeutic relational agent for reducing substance misuse during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic disrupted access to treatment for substance use disorders (SUDs), while alcohol and cannabis retail sales increased. During the pandemic, we tested a tailored digital health solution, Woebot-SUDs (W-SUDs), for reducing substance misuse. Methods In a randomized controlled trial, we compared W-SUDs for 8 weeks to a waitlist control. U.S. adults (N = 180) who screened positive for substance misuse (CAGE-AID>1) were enrolled June–August 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…However, two studies showed that users could potentially build a bond with chatbot apps. A study of the app Woebot (a therapeutic chatbot that delivers CBT), which was used to reduce substance misuse during the COVID-19, found that the bond subscale rating was higher than task and goal subscales ratings ( 50 ). Similarly, another study with Woebot found that the bond subscale rating was high and comparable to face-to-face therapy ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two studies showed that users could potentially build a bond with chatbot apps. A study of the app Woebot (a therapeutic chatbot that delivers CBT), which was used to reduce substance misuse during the COVID-19, found that the bond subscale rating was higher than task and goal subscales ratings ( 50 ). Similarly, another study with Woebot found that the bond subscale rating was high and comparable to face-to-face therapy ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the types of usage data in these two studies were different. Clarke et al ( 14 ) measured number of program interactions (i.e., logins), number of modules completed, and frequency of self-monitoring, while Prochaska et al ( 50 ) measured days used, in-app text messages, and completed modules. In addition, Goldberg et al ( 49 ) adopted self-report usage frequency as engagement in study 1, and adopted usage data in study 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can cause the body to quickly produce a large number of cytokines, such as IL-6, IL-12, IL-8, and IFN-α; this abnormal increase in the number of cytokines can cause aggregation of eosinophils and other infectious lesions. The organs and tissues are also severely damaged in the process of effectively eradicating the infection ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the objective of the study by Prochaska et al [17 ▪ ] was to tackle the disrupted access to treatments for SUDs during the COVID-19 pandemic and add to the growing body of literature on the use of automated chatbots. For this reason, the authors assessed the effectiveness of an automated self-help coach that delivers CBT in the format of brief, daily text-based conversations via a mobile application.…”
Section: Add-on Interventionsmentioning
confidence: 99%